A carbon dioxide gas-sensitive material based on praseodymium lanthanum iron cobalt oxide and its application
By doping Pr and Co elements into LaFeO3 material, carbon dioxide gas-sensitive material of PrxLa1-xFe1-yCoyO3 was prepared, which solved the problem of insufficient sensitivity and selectivity of existing materials for carbon dioxide gas detection, and achieved the effect of efficient detection of CO2 gas at lower temperatures.
Patent Information
- Application Number
- CN202411474565.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The existing lanthanum ferrite materials have low selectivity and sensitivity to carbon dioxide gas, making it difficult to effectively detect CO2 gas at lower temperatures.
By doping Pr element at the A position of LaFeO3 material and doping Co element at the B position, a carbon dioxide gas-sensitive material of PrxLa1-xFe1-yCoyO3 was prepared, and the nanoparticle structure was prepared by the sol-gel method.
It achieves excellent selectivity and sensitivity to CO2 gas, reduces the operating temperature of the sensor to 100-220°C, reduces energy consumption, and is suitable for portable or low-power devices.
Smart Images

Figure CN119044257B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon dioxide gas sensors, and in particular to a carbon dioxide gas-sensitive material based on praseodymium lanthanum iron cobalt oxide and application thereof. Background Art
[0002] Carbon dioxide (CO2), as a common greenhouse gas, has brought negative impacts on agriculture, economy, marine ecology, water cycle and environment. At the same time, CO2 can be used for other purposes to serve human life and economic development. Therefore, the detection of its concentration is of great significance in industry, environmental protection and control of greenhouse effect.
[0003] At present, gas sensors are the main means for detecting CO2 gas, which utilizes the electrical properties of gas-sensitive materials to detect gas concentrations and converts gas concentrations into detectable signals. In the prior art, carbon dioxide gas-sensitive materials mainly include perovskite oxide materials, semiconductor metal oxide materials, and organic polymer materials. Among them, perovskite oxide materials have shown broad application prospects in the field of gas sensors due to their unique electrical properties, structural stability, and good gas-sensitive properties. Doping is a method of giving perovskite oxide materials higher gas sensing performance, especially the doping substitution of A-site elements and B-site elements in perovskite oxide materials affects the gas-sensitive properties of the material.
[0004] In the prior art, the paper "Modification of lanthanum ferrite-based materials and research on their gas-sensing properties" (Shanghai University of Technology, Liang Shuang, May 2023) discloses the preparation of Co-doped LaFeO3 materials by hydrothermal and post-calcination methods. Compared with pure lanthanum ferrite materials, the response speed and selectivity of Co-doped lanthanum ferrite are faster, and its response value to acetone gas reaches 77.7. The paper "Optimization of Acetone and Ethylene Glycol Methyl Ether Gas Sensing Properties of LaFeO3 Nanoparticles" (Taiyuan University of Technology, Feng Yibiao, June 2022) discloses Pr-doped lanthanum ferrite nanoparticles, using lanthanum nitrate, iron nitrate, praseodymium nitrate, anhydrous citric acid and polyethylene glycol as raw materials to prepare LaFeO3 nanoparticles by sol-gel method. 1-x Pr x The addition of FeO3 nanoparticles and Pr can significantly improve the response value of lanthanum ferrite to acetone and ethylene glycol methyl ether, reduce the optimal working temperature and shorten the response / recovery time. However, the nanoparticles obtained by doping and modifying the lanthanum ferrite material above all have high selectivity for acetone gas, but do not show high selectivity and sensitivity for carbon dioxide.
[0005] Therefore, suitable elements are selected to dope the lanthanum ferrite material at the A-site and the B-site to obtain a gas-sensitive material for CO2 gas detection, so as to reduce the working temperature during detection and improve the detection sensitivity. Summary of the invention
[0006] In view of the above-mentioned prior art, the object of the present invention is to provide a carbon dioxide gas-sensitive material based on praseodymium lanthanum iron cobalt oxide and its application. The chemical formula of the carbon dioxide gas-sensitive material based on praseodymium lanthanum iron cobalt oxide is Pr x La 1-x Fe 1- y Co y O3, where 0 < x ≤ 0.5 and 0 < y ≤ 0.5. The nanoparticle structure of the carbon dioxide gas-sensitive material provides more active sites. Its preparation method is as follows: Using the sol-gel method, by doping Pr element at the A site and Co element at the B site of the LaFeO3 material, through the composite doping design of the A site and the B site, the prepared carbon dioxide gas-sensitive material shows excellent sensitivity in detecting CO2 gas, can effectively distinguish CO2 gas from other interfering gases. At the same time, the carbon dioxide gas-sensitive material prepared by the present invention can reduce the working temperature of the sensor to 100 - 220 °C, reduce the energy consumption of the sensor, and is suitable for portable or low-power devices.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] In the first aspect of the present invention, there is provided a carbon dioxide gas-sensitive material based on praseodymium lanthanum iron cobalt oxide, and the chemical formula of the carbon dioxide gas-sensitive material is Pr x La 1-x Fe 1-y Co y O3, where 0 < x ≤ 0.5 and 0 < y ≤ 0.5.
[0009] Preferably, the average particle size of the carbon dioxide gas-sensitive material based on praseodymium lanthanum iron cobalt oxide is 70 - 150 nm.
[0010] In the second aspect of the present invention, there is provided a preparation method of a carbon dioxide gas-sensitive material based on praseodymium lanthanum iron cobalt oxide, including the following steps:
[0011] (1) Mix praseodymium oxide, lanthanum nitrate, iron nitrate, cobalt nitrate and citric acid to obtain a mixture, dissolve the mixture in dilute nitric acid with a mass fraction of 8 - 9% and stir to make it uniform to obtain a mixed solution;
[0012] The addition amount ratio of praseodymium oxide, lanthanum nitrate, iron nitrate, cobalt nitrate, citric acid and dilute nitric acid is (0.01 - 3) mol : (0.05 - 3) mol : (0.01 - 3) mol : (0.1 - 50) g : (10 - 80) g : (100 - 200) mL;
[0013] (2) The mixed solution is heated and stirred, and then cooled to room temperature to obtain a gel; the gel is calcined and ground to obtain the carbon dioxide gas-sensitive material Pr x La 1-x Fe 1-y Co y O3;
[0014] The heating temperature is 50-85°C, the stirring time is 2-8h, the calcination temperature is 650-950°C, and the calcination time is 3-10h.
[0015] Preferably, in step (1), the stirring time is 6-12 hours.
[0016] Preferably, in step (2), the heating method is water bath heating.
[0017] Preferably, in step (2), the stirring speed is 500-1000 r / min.
[0018] Preferably, in step (2), the grinding time is 2-6 hours.
[0019] The third aspect of the present invention provides the use of a carbon dioxide gas-sensitive material based on praseodymium lanthanum iron cobalt oxide in detecting carbon dioxide gas and / or preparing a carbon dioxide gas-sensitive sensor.
[0020] Preferably, the carbon dioxide gas concentration is 2500-3500 ppm.
[0021] Preferably, a carbon dioxide gas-sensitive material based on praseodymium lanthanum iron cobalt oxide, deionized water and pinene alcohol are mixed in an amount of (1-3) g: (3-9) mL: (1-3) mL to obtain a slurry; the slurry is spin-coated on an alumina substrate to form a gas-sensitive film with a thickness of 80-200 μm, and the gas-sensitive film is aged at 200-240° C. for 10-24 h to obtain a carbon dioxide gas-sensitive sensor.
[0022] Beneficial effects of the present invention:
[0023] The present invention prepares Pr by combining praseodymium, lanthanum, iron and cobalt. x La 1-x Fe 1-y Co yO3 perovskite oxide material is used as a carbon dioxide gas-sensitive material. Among them, Pr element dopes the LaFeO3 material at the A position, and Co element dopes the LaFeO3 material at the B position. Through the composite doping design of the A position and the B position, the prepared carbon dioxide gas-sensitive material shows excellent sensitivity in detecting CO2 gas, and can effectively distinguish CO2 gas from other interfering gases. At the same time, the carbon dioxide gas-sensitive material prepared by the present invention can reduce the operating temperature of the sensor to 100-220°C, reduce the energy consumption of the sensor, and is suitable for portable or low-power devices.
[0024] The nanoparticle structure of the carbon dioxide gas-sensitive material prepared by the present invention provides more active sites, effectively improving the gas adsorption and reaction speed, so that the response time of the carbon dioxide gas-sensitive sensor to CO2 is only tens of seconds. At the same time, the sol-gel method used by the present invention to prepare the carbon dioxide gas-sensitive material has a simple and controllable process, and the material shows good stability in long-term use. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 : XRD pattern of the carbon dioxide gas-sensitive material based on praseodymium lanthanum iron cobalt oxide prepared in Example 1;
[0026] Figure 2 : SEM image of the carbon dioxide gas-sensitive material based on praseodymium lanthanum iron cobalt oxide prepared in Example 1;
[0027] Figure 3 : EDS image of the carbon dioxide gas-sensitive material based on praseodymium lanthanum iron cobalt oxide prepared in Example 1;
[0028] Figure 4 : The relationship between the gas-sensing performance and temperature of the carbon dioxide gas-sensitive materials prepared in Example 1 and Comparative Examples 1-3 to 3000ppm CO2 gas;
[0029] Figure 5 : Schematic diagram of the response of the carbon dioxide gas-sensitive material prepared in Example 1 to 3000 ppm of various gases. DETAILED DESCRIPTION
[0030] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0031] At present, perovskite oxide materials have broad application prospects in the field of gas sensors due to their good gas-sensing properties. In order to further improve the gas-sensing properties of LaFeO3 materials, doping of A-site elements and B-site elements is often carried out. In the prior art, although Pr element is used for A-site doping of LaFeO3 materials and Co element is used for B-site doping of LaFeO3 materials, the gas-sensing materials obtained after doping have high selectivity and sensitivity to acetone gas and do not show good selectivity and sensitivity to CO2 gas.
[0032] Based on this, the present invention provides a carbon dioxide gas-sensing material Pr x La 1-x Fe 1-y Co y O3, where 0 < x ≤ 0.5 and 0 < y ≤ 0.5. The carbon dioxide gas-sensing material has a nanoparticle structure with an average particle size of 70 - 150 nm. When the carbon dioxide gas-sensing material is used for carbon dioxide gas detection, when it contacts with CO2, due to the adsorption and surface reaction of gas molecules, the conductivity of the carbon dioxide gas-sensing material changes, thereby detecting the concentration of carbon dioxide.
[0033] In the present invention, a carbon dioxide gas-sensing material is obtained by doping Pr element and Co element into LaFeO3 material. The doping of Pr and Co elements optimizes the electron transport and oxygen vacancy structure of the carbon dioxide gas-sensing material, so that the carbon dioxide gas-sensing material can have good conductivity and gas-sensing responsiveness at a lower temperature, especially excellent selectivity and sensitivity to CO2 gas. The transition metal action of Fe and Co in the carbon dioxide gas-sensing material enhances the redox ability of the material, enabling the material to respond and recover quickly, and is suitable for high-efficiency and low-power carbon dioxide sensor applications. Structurally, the lattice structure of the carbon dioxide gas-sensing material prepared in the present invention ensures that when it contacts with CO2 gas, the redox reaction can proceed rapidly, thereby improving the sensitivity and selectivity of CO2 gas detection.
[0034] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with specific embodiments.
[0035] The experimental materials used in the embodiments of the present invention are all conventional experimental materials in the art and can be obtained through commercial channels.
[0036] Example 1: Preparation of carbon dioxide gas-sensing material Pr 0.2 La 0.8 Fe 0.7 Co 0.3 O3
[0037] (1) After mixing praseodymium trioxide, lanthanum nitrate, ferric nitrate, cobalt nitrate and citric acid to obtain a mixture, the mixture is dissolved in 8.5% by mass dilute nitric acid and stirred for 9 hours to mix well to obtain a mixed solution, wherein the added amount ratio of praseodymium trioxide, lanthanum nitrate, ferric nitrate, cobalt nitrate, citric acid and dilute nitric acid is 3.30 g: 25.99 g: 16.93 g: 5.48 g: 50 g: 100 mL;
[0038] (2) The mixed solution was heated in a water bath at 80°C and stirred at 600 r / min for 8 h. After cooling to room temperature, a gel was obtained. The gel was calcined at 850°C for 8 h and ground for 3 h to obtain the carbon dioxide gas-sensitive material Pr 0.2 La 0.8 Fe 0.7 Co 0.3 O3.
[0039] Example 2: Carbon dioxide gas-sensitive material based on praseodymium lanthanum iron cobalt oxide 0.1 La 0.9 Fe 0.9 Co 0.1 Preparation of O3
[0040] (1) After mixing praseodymium trioxide, lanthanum nitrate, ferric nitrate, cobalt nitrate and citric acid to obtain a mixture, the mixture is dissolved in 8% by mass dilute nitric acid and stirred for 6 hours to mix well to obtain a mixed solution, wherein the added amount ratio of praseodymium trioxide, lanthanum nitrate, ferric nitrate, cobalt nitrate, citric acid and dilute nitric acid is 1.65g:29.25g:21.76g:1.83g:40g:120mL;
[0041] (2) The mixed solution was heated in a water bath at 50°C and stirred at a speed of 500 r / min for 2 h. After cooling to room temperature, a gel was obtained. The gel was calcined at 650°C for 3 h and ground for 2 h to obtain the carbon dioxide gas-sensitive material Pr 0.1 La 0.9 Fe 0.9 Co 0.1 O3.
[0042] Example 3: Carbon dioxide gas-sensitive material based on praseodymium lanthanum iron cobalt oxide 0.5 La 0.5 Fe 0.5 Co 0.5 Preparation of O3
[0043] (1) After mixing praseodymium trioxide, lanthanum nitrate, ferric nitrate, cobalt nitrate and citric acid to obtain a mixture, the mixture is dissolved in 9% by mass dilute nitric acid and stirred for 12 hours to mix well to obtain a mixed solution, wherein the added amount ratio of praseodymium trioxide, lanthanum nitrate, ferric nitrate, cobalt nitrate, citric acid and dilute nitric acid is 8.25g:16.25g:12.1g:9.15g:60g:150mL;
[0044] (2) The mixed solution was heated in a water bath at 85°C and stirred at a speed of 1000 r / min for 6 h. After cooling to room temperature, a gel was obtained. The gel was calcined at 950°C for 10 h and ground for 6 h to obtain the carbon dioxide gas-sensitive material Pr 0.5 La 0.5 Fe 0.5 Co 0.5 O3.
[0045] Example 4: Preparation of carbon dioxide gas sensor
[0046] The carbon dioxide gas-sensitive material prepared in Example 1, deionized water and pine alcohol were mixed in an addition ratio of 1 g: 3 mL: 1 mL to obtain a slurry, which was spin-coated on the surface of an aluminum oxide ceramic tube at a rotation speed of 500 rpm to form a 136 μm gas-sensitive film, and the gas-sensitive film was placed in air and aged at 220° C. for 20 h to obtain a carbon dioxide gas-sensitive sensor.
[0047] Comparative Example 1: Preparation of carbon dioxide gas-sensitive material
[0048] The difference between this comparative example and Example 1 is that in step (1), cobalt nitrate and praseodymium trioxide are not added, and the obtained carbon dioxide gas-sensitive material is LaFeO3.
[0049] Comparative Example 2: Preparation of carbon dioxide gas-sensitive material
[0050] The difference between this comparative example and Example 1 is that in step (1), praseodymium trioxide is not added, and the obtained carbon dioxide gas-sensitive material is LaFe 0.7 Co 0.3 O3.
[0051] Comparative Example 3: Preparation of Carbon Dioxide Gas Sensitive Material
[0052] The difference between this comparative example and Example 1 is that in step (1), cobalt nitrate is not added, and the obtained carbon dioxide gas-sensitive material is Pr 0.2 La 0.8 FeO3.
[0053] Test Example 1: Structural Characterization
[0054] The carbon dioxide gas-sensitive material prepared in Example 1 was characterized by the following structure: Figure 1-Figure 3 shown.
[0055] Figure 1 is the XRD pattern of the carbon dioxide gas-sensitive material prepared in Example 1. Figure 1 It can be seen that the crystallization peaks correspond to the (101), (121) and (202) phases of LaFeO3 (NO. 37-1493). Figure 2 The SEM images of the carbon dioxide gas-sensitive material prepared in Example 1 at 30K, 60K and 100K magnifications are shown in FIG. Figure 2 It can be seen that the carbon dioxide gas-sensitive material presents a typical nanoparticle structure, the material has a large specific surface area and porosity, and there are more reaction sites and transmission channels for gas molecules. Figure 3 The EDS diagram of the carbon dioxide gas-sensitive material prepared in Example 1 is shown in FIG. Figure 3 It can be seen that Pr and Co elements exist in the carbon dioxide gas-sensitive material, which shows that Pr and Co elements are successfully doped.
[0056] Test Example 2: Gas Sensing Performance Test
[0057] The carbon dioxide gas-sensitive materials prepared in Example 1 and Comparative Examples 1-3 were coated on the sensing film, and the gas-sensitive responses (Rg / Ra) to 3000ppm of CO2, C2H7N and other gases were tested. The results are as follows: Figure 4-Figure 5 As shown. Among them, Ra is the resistance of the sensor in the air, and Rg is the resistance of the gas being measured. The experimental environment is: RH is 20%, and the ambient temperature is 20℃.
[0058] Depend on Figure 4 It can be seen that the optimal working temperature of the carbon dioxide gas-sensitive material prepared by the present invention is 180°C. At the working temperature of 180°C, the response value of the carbon dioxide gas-sensitive material prepared by the present invention to 3000ppm of CO2 gas is 2.13, the response value of the carbon dioxide gas-sensitive material LaFeO3 prepared in Comparative Example 1 to 3000ppm of CO2 gas is 1.58, and the carbon dioxide gas-sensitive material LaFeO3 prepared by only using Co element to dope the LaFeO3 material at B position in Comparative Example 2 is 1.54. 0.7 Co 0.3 The response value of O3 to 3000ppm CO2 gas is 1.67. In Comparative Example 3, only Pr element is used to dope LaFeO3 material at A position to obtain the carbon dioxide gas-sensitive material Pr. 0.2 La 0.8 Fe 0.7The response value of O3 to 3000ppm CO2 gas is 1.73. It can be seen that by doping Pr element at the A position and Co element at the B position of LaFeO3 material, there is a synergistic effect in improving the response value of carbon dioxide gas-sensitive material to CO2 gas.
[0059] Depend on Figure 5 It can be seen that when exposed to multiple gases, the carbon dioxide gas-sensitive material Pr 0.2 La 0.8 Fe 0.7 Co 0.3 The selectivity of O3 to CO2 gas is significantly higher than that of gases including C7H8, C2H7N, etc., which shows that the gas-sensitive material prepared by the present invention has good selectivity to carbon dioxide gas.
[0060] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. An application of a carbon dioxide gas-sensitive material based on praseodymium lanthanum iron cobalt oxide in detecting carbon dioxide gas and / or preparing a carbon dioxide gas-sensitive sensor, characterized in that: The chemical formula of the carbon dioxide gas-sensitive material is Pr x La 1-x Fe 1- y Co y O3, where 0 < x ≤ 0.5, 0 < y ≤ 0.
5. The carbon dioxide gas-sensitive material has a nanoparticle structure with an average particle size of 70 - 150 nm; The carbon dioxide gas-sensitive material is prepared by the following method: (1) mixing praseodymium trioxide, lanthanum nitrate, iron nitrate, cobalt nitrate and citric acid to obtain a mixture, dissolving the mixture in 8-9% by mass dilute nitric acid and stirring to mix the mixture to obtain a mixed solution; The added amount ratio of praseodymium trioxide, lanthanum nitrate, ferric nitrate, cobalt nitrate, citric acid and dilute nitric acid is (0.01-3) mol: (0.05-3) mol: (0.01-3) mol: (0.1-50) g: (10-80) g: (100-200) mL; (2) The mixed solution is heated and stirred, and then cooled to room temperature to obtain a gel; the gel is calcined and ground to obtain the carbon dioxide gas-sensitive material Pr x La 1-x Fe 1-y Co y O3; The heating temperature is 50-85°C, and the stirring time is 2-8h; the calcination temperature is 650-950°C, and the calcination time is 3-10h.
2. The use according to claim 1, characterized in that The carbon dioxide gas concentration is 2500-3500ppm.
3. The use according to claim 1, characterized in that The carbon dioxide gas sensor is prepared by the following method: A carbon dioxide gas-sensitive material based on praseodymium lanthanum iron cobalt oxide, deionized water and pinene alcohol are mixed in the ratio of (1-3) g: (3-9) mL: (1-3) mL to obtain a slurry; the slurry is spin-coated on an alumina substrate to form a gas-sensitive film with a thickness of 80-200 μm; the gas-sensitive film is aged at 200-240° C. for 10-24 h to obtain a carbon dioxide gas-sensitive sensor.
Citation Information
Patent Citations
CO2 gas sensing material as well as preparation method and application thereof
CN102617125A
LaFeO3-based ethanol gas sensor with high gas-sensitive property and preparation method thereof
CN108152337A
Gas-sensitive nano material and preparing method thereof
CN1528659A